Divergent climate change effects on widespread dryland plant communities driven by climatic and ecohydrological gradients. (26th July 2021) - Palmquist, Kyle A.; Schlaepfer, Daniel R.; Renne, Rachel R.; Torbit, Stephen C.; Doherty, Kevin E.; Remington, Thomas E.; Watson, Greg; Bradford, John B.; Lauenroth, William K.
Abstract: Plant community response to climate change will be influenced by individual plant responses that emerge from competition for limiting resources that fluctuate through time and vary across space. Projecting these responses requires an approach that integrates environmental conditions and species interactions that result from future climatic variability. Dryland plant communities are being substantially affected by climate change because their structure and function are closely tied to precipitation and temperature, yet impacts vary substantially due to environmental heterogeneity, especially in topographically complex regions. Here, we quantified the effects of climate change on big sagebrush ( Artemisia tridentata Nutt.) plant communities that span 76 million ha in the western United States. We used an individual‐based plant simulation model that represents intra‐ and inter‐specific competition for water availability, which is represented by a process‐based soil water balance model. For dominant plant functional types, we quantified changes in biomass and characterized agreement among 52 future climate scenarios. We then used a multivariate matching algorithm to generate fine‐scale interpolated surfaces of functional type biomass for our study area. Results suggest geographically divergent responses of big sagebrush to climate change (changes in biomass of −20% to +27%), declines in perennial C3 grass and perennial forb biomass in most sites, and widespread, consistent, and sometimes large increases in perennial C4 grasses. The largest declines in big sagebrush, perennial C3 grass and perennial forb biomass were simulated in warm, dry sites. In contrast, we simulated no change or increases in functional type biomass in cold, moist sites. There was high agreement among climate scenarios on climate change impacts to functional type biomass, except for big sagebrush. Collectively, these results suggest divergent responses to warming in moisture‐limited versus temperature‐limited sites and potential shifts in the relative importance of some of the dominant functional types that result from competition for limiting resources. Abstract : Dryland plant community response to climate change results from the competitive interactions of multiple species for limiting soil water resources, yet climate impacts are likely to vary substantially due to environmental heterogeneity. We quantified the effects of climate change on big sagebrush plant communities throughout the western United States using an individual‐based plant simulation model that represents competition for soil water resources. Our results suggest divergent responses of big sagebrush to warming in moisture‐limited vs. temperature‐limited sites and potential shifts in the relative importance of perennial C3 and perennial C4 grasses when disturbances are minimized.